Fabrication of Fe-Cu composites from electroexplosive bimetallic nanoparticles by spark plasma sintering; Vacuum; Vol. 170 - Lozhkomoev A. S. Aleksandr Sergeevich; Pervikov A. V. Alexander Vasilyevich; Chumaevsky A. V. Andrey Valerjevich; Dvilis E. S. Edgar Sergeevich; Paygin V. D. Vladimir Denisovich; Khasanov O. L. Oleg Leonidovich; Lerner M. I. Marat Izrailyevich (2019, 2019)
Title screen